Unearthing the relationship between disease and causation in South African gold mines - De Waal, Lisa (Department of Private Law, 2017)
The purpose of this dissertation is to present an analysis of the relationship between the law of delict – specifically the element of factual causation – and the manner in which this element should apply to an assessment of the liability of gold mining companies in South Africa and their failure to protect mineworkers from exposure to silicosis, silico-tuberculosis and pulmonary tuberculosis. It is argued that the Constitutional Court's interpretation, and their ultimate application of the test for factual causation in Lee v Correctional Services 2013 (2) SA 144 (CC), in the form of the material increase of risk test, is precedent for the assessment of factual causation within the tuberculosis class in Nkala and Others v Harmony Gold Mining Co Ltd and Others 2016 (5) SA 240 (GJ). To underscore this argument, analogies are drawn between the powerful positions of gold mining companies and the State, and the vulnerable positions of mineworkers and prisoners in South Africa, as well as the Constitutional obligations owed by the State and gold mining companies towards prisoners and mineworkers, respectively. Furthermore, reasons why the material contribution test should apply to the silicosis class are discussed. This dissertation also outlines the statutory and common law duties owed by mining companies to underground mineworkers, for establishing these requirements is a requirement of the material increase of risk and material contribution tests. It is noted that the trial court in the Nkala class action suit should apply the aforementioned tests for factual causation to the two classes, failing which would be an injustice to legal precedent, and would be unfair and unreasonable.